Food security status and childhood obesity in Kuantan Pahang - Mat Ya, Roselawati; Mohd Abu Bakar, Wan Azdie; Afandi, Aflah; Ab Rahman, Jamalludin; Mohd Shariff, Zalilah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Introduction: Food insecurity has become one of the concerning issues in public health. The purpose of this study was to investigate household food security status and its relationship with childhood obesity in Kuantan, Pahang.